Low Wear Rate Selection of Nylon 6-Boron Nitride (PA6/BN) Composite During Composite Development Using Grey Relational Analysis Through the Direct and Indirect Factors of Taguchi Method - Adekoya, Abdulganiyu Adegboyega; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola; Aderibigbe, Samuel Bolaji; Odudare, Samson Oluwaseun (International Journal of Industrial Engineering and Engineering Management, 2024)
Wear performance has been evaluated for mechanical equipment using normal load, sliding speed, and sliding distance, but aspect ratios have been traditionally ignored in the literature. Also, limited studies have analyzed wear performance with sparse information. In this study, a grey relational analysis (GRA) technique is proposed for the wear performance analysis of nylon 6/boron nitride composite using aspect ratios. A complete divergence is made from the literature where the aspect ratios of the particulate weight of the composite, normal load, sliding speed, and sliding distance are treated in direct and aspect ratios of 12 cases where the reciprocals of factors, their squares and cubes are considered. Results show that the proposed method of GRA is feasible and offers an adequate illustration of the indices of the parameters of the wear process as opposed to the present method of Taguchi that exists in the literature. A key result is from case 2, which shows that experimental trial 9 with the grey relational grade of 1.00 has the lowest wear rate. The corresponding values of the parameters are 0.05 of the 1/NL parameter, while the SD parameter is 500. This is interpreted as 0.05N-1 of the reciprocal of normal load and 500m for the sliding distance. The principal contribution of this research is the introduction of the grey relational analysis to reduce the wear rate of nylon 6-boron nitride composite. The proposed method is useful as a planning tool for the maintenance engineer to monitor the health of equipment in practice.